2016
DOI: 10.1097/ccm.0000000000001637
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 Stimulation Attenuates Ischemic Liver Injury and Enhances Mitochondrial Recovery and Autophagy

Abstract: Objective Hepatic ischemia-reperfusion (I/R) is a major clinical problem with limited treatment options. The pathophysiology of hepatic I/R is characterized by mitochondrial dysfunction and cellular energy deficits. Sirtuin 1 (Sirt1) is an energy-sensing enzyme known to modulate mitochondrial biogenesis. We hypothesized that pharmacologic activation of Sirt1 is protective after hepatic I/R injury. Design Animal study. Setting University-based experimental laboratory. Subjects Wild-type C57BL/6 mice. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 59 publications
1
45
0
Order By: Relevance
“…These NRFs activate TFAM, which drives mitochondrial gene transcription and genome replication (Ventura‐Clapier et al ., ). In rat primary hepatocytes subjected to H/R, TFAM protein levels decreased along with mitochondrial mass and membrane potential decrease (Khader et al ., ). Interestingly, in our study, the levels of PGC1α, NRF1 and TFAM protein expression and mtDNA copy number were reduced by IR, and RvD1 attenuated these changes, suggesting that RvD1 activates mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…These NRFs activate TFAM, which drives mitochondrial gene transcription and genome replication (Ventura‐Clapier et al ., ). In rat primary hepatocytes subjected to H/R, TFAM protein levels decreased along with mitochondrial mass and membrane potential decrease (Khader et al ., ). Interestingly, in our study, the levels of PGC1α, NRF1 and TFAM protein expression and mtDNA copy number were reduced by IR, and RvD1 attenuated these changes, suggesting that RvD1 activates mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Second, we assessed mitochondrial function indirectly by measuring ATP and ADP levels in the tissue. While this is a standard approach in ischemia-reperfusion models 14,17 , alternative techniques to directly measure mitochondrial function such as high resolution respirometry may provide more precision. Finally, due to the limited availability of old rats, we included 2 strains (Lewis and ACI), with the ACI strain serving as the untreated control.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, we previously have demonstrated that SRT1720 treatment inhibits oxidative stress, reduces apoptosis, and restores mitochondrial integrity in the liver of mice after hepatic ischemia-reperfusion injury. 15 Upregulation of Sirt1 has also been shown to inhibit apoptosis and protect against oxidative stress, ameliorating hepatic steatosis and acute liver injury. 44 Therefore, SRT1720 may act through Sirt1 to attenuate the ROS production and maintain mitochondrial homeostasis, leading to downregulation of the of NLRP3 activation in the liver of septic mice.…”
Section: Discussionmentioning
confidence: 99%
“…11 Activation of Sirt1has been demonstrated to improve metabolism in murine models of cardiac, renal, intestinal, and hepatic ischemia-reperfusion injury. 12-15 In addition to its role in metabolic modulation, Sirt1 has also played a direct role in regulating inflammation, 16 such as by modulating the activity of nuclear factor kappa B (NF-κB), a critical transcription factor in the regulation of proinflammatory cytokine production. 17 …”
Section: Introductionmentioning
confidence: 99%